Challenges in Implementing Sustainable Forest Management in the Era of Globalization in Indonesia - Imburi, Christian Soleman; Angrianto, Novaldi Laudi (Westscience Press, 2025)
This study examines the challenges of implementing Sustainable Forest Management (SFM) in Indonesia within the rapidly evolving context of globalization. Using a qualitative literature review of 10 Scopus-indexed articles, the analysis identifies key obstacles that hinder effective and sustainable forest governance. The findings reveal that institutional weaknesses—such as fragmented policies, weak law enforcement, and limited coordination among governmental agencies—remain central barriers. Economic pressures driven by global market demands for timber and agricultural commodities intensify deforestation risks and complicate the alignment between development goals and conservation priorities. Social challenges, including limited community participation, land tenure conflicts, and uneven distribution of benefits, further constrain the success of SFM initiatives. Additionally, environmental degradation, climate change impacts, and insufficient adoption of advanced monitoring technologies continue to undermine forest protection efforts. Global sustainability frameworks and certification schemes, while beneficial, introduce complex requirements that local stakeholders often struggle to meet. This study concludes that addressing SFM challenges in Indonesia requires strengthening institutional capacity, enhancing community empowerment, aligning economic incentives with conservation goals, and integrating advanced technologies to support evidence-based policymaking.